EFFORTS TO IMPROVE TEACHERS' CAPABILITIES IN MAKING EQUIPMENT OF ONLINE LEARNING DEVICES THROUGH THE SUPERVISION OF THE PRINCIPAL IN SD 14 PAUH TIMUR - Wismawati Wismawati (JOURNAL INTERNATIONAL ON GLOBAL EDUCATION, 2022)
The purpose of this school action research is to find out the improvement of teachers' abilities in making online learning tools complete through the supervision of the Principal at SD Negeri 14 Pauh Timur in the 2020/2021 academic year. Based on the results of the analysis and discussion of cycle I and cycle II above, it can be concluded that: Through the supervision of the Principal at SD Negeri 14 Pauh Timur in the 2020/2021 school year, the ability of teachers to make online learning tools complete has increased significantly. If in the first cycle the total average value of the teacher's competence only increased from the first cycle, namely the percentage of completeness 66.67% and 88.89% in the second cycle the teacher was generally said to be complete with the total increase in the teacher's average score was 8.67 and the total percentage increase is 22.22%, this shows the improvement efforts made by researchers in the second cycle bring changes. Academic supervision is effectively used to increase teacher competence at SD Negeri 14 Pauh Timur in making online learning tools complete.